How are apprentice satisfaction and concerns changing as a consequence of the coronavirus pandemic? - Melanie Hochmuth; Alina Nadine Geßler; Silke Seyffer; Andreas Frey (Social Sciences and Humanities Open, 2022)
For more than a year, the coronavirus pandemic has severely restricted everyday life. This has had an impact on the economy, on working life and on the organisation of school routines. Apprentices in dual vocational training have been doubly challenged as they have had to cope with changes both at work and at vocational school. Therefore, it is worthwhile to explore what psychosocial consequences the coronavirus pandemic has had on apprentices. However, little research has been conducted on the impact of the pandemic on the worries and life satisfaction for apprentices in general. This mixed-methods study fills this research gap by using data from 167 apprentices (16–35 years old) in technical and commercial trade apprenticeships in Southern Germany. When designing the survey, particular attention was paid to a visual presentation of Likert scales suitable for adolescents to assess their worries and satisfaction during and prior to the coronavirus pandemic. Explicit questions were asked about their satisfaction with work, social contacts and life in general, as well as their concerns about their financial situation, job loss and health. Furthermore, these aspects are analysed with respect to gender differences based on the assumption that the coronavirus pandemic has a different impact on the satisfaction and worries of women and men. The results show that apprentices’ worries significantly increased with their satisfaction decreasing and that women were particularly affected.